1998
DOI: 10.1190/1.1444431
|View full text |Cite
|
Sign up to set email alerts
|

Shallow to very shallow, high‐resolution reflection seismic using a portable vibrator system

Abstract: In shallow engineering-geophysical applications, there is a lack of controlled, nondestructive, high-resolution mapping tools, particularly for the target depth that ground-penetrating radar cannot reach but which is too shallow for other conventional geophysical methods. For soft soil, this corresponds to a depth of 2 to 30 m. We have developed a portable, high-frequency P-wave vibrator system that is capable of bridging this gap. As far as the important contribution of the seismic source is concerned, penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 17 publications
(15 reference statements)
0
31
0
Order By: Relevance
“…6). Another advantage of the vibroseis technique is that, compared to impulse sources, the emitted highprecision frequency-modulated signal generates a repeatable and consistent wavelet (Klauder et al, 1960;Goupillaud, 1976;Nijhof et al, 1998;Drijkoningen, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…6). Another advantage of the vibroseis technique is that, compared to impulse sources, the emitted highprecision frequency-modulated signal generates a repeatable and consistent wavelet (Klauder et al, 1960;Goupillaud, 1976;Nijhof et al, 1998;Drijkoningen, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the estimated shear wave velocity correlates well with subsurface lithology. Also, the propagating shear waves often have a shorter wavelength in these soils compared to that of P-waves (Ghose et al, 1998;Haines and Ellefsen, 2010). This results in better resolution when imaging with shear waves.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ghose et al (1998) found that it is easier to generate high frequencies on hard ground, like asphalt, than on soft soil, because the former has greater radiation impedance.…”
Section: Field Data Acquisitionmentioning
confidence: 99%